COMPARISON OF KNOWLEDGE IN THE FIELD OF NUTRITIONAL FATS AMONG STUDENTS - Małgorzata Kowalska (Chiriotti Editori, 2015)
The aim of this work was to analyze the knowledge in the field of trans fatty acids (TFAs) and nutritional recommendations related to fats among students at the University of Life Sciences in Warsaw (SGGW) and Wageningen (WUR). The research was done using a questionnaire composed of 16 questions among 194 students from SGGW and WUR in 2012. In Poland 96% and in Holland 89% of students had heard the name "trans fat". More than half of the questionnaire respondents knew industrial sources of TFAs. After comparing the results of the research, in which students succeeded, it was concluded that differences in the level of knowledge were statistically not significant (p<0.05). Eating habits for fatty pastry products representing a potential source of TFAs were similar. WUR students' purchase of pastry products was dependent on price, whereas that of Polish students depended on information and ingredients listed on the package.